Influence of Inheritance Tax on the Size of Shadow Economy and the Volume of Tax Evasion - Linseis, Philippe (Journal of Legal Studies, 2022)
The objective of the paper is to investigate the influence of the inheritance tax on the amount of tax evasion in different countries. The inheritance tax is among the most unpopular taxes. It is assumed, that unpopular taxes, such as the inheritance tax, have a measurable influence on the amount of tax evasion. Countries that levy inheritance taxes and countries which don’t levy inheritance taxes are compared in their success in fighting the shadow economy over a longer period (1991 – 2017). For that, data from Medina and Schneider from 2019 about the development of the shadow economy and from the OECD about the inheritance tax revenue is used. The approach is, to find dependencies between the inheritance tax revenue and the size of the shadow economy. The results show, that countries which abolished the inheritance tax, are not anymore that successful in fighting tax evasion than they were before. There is also evidence, that countries with a relatively high inheritance tax revenue are not able to fight tax evasion to the same extent, as countries that levy relatively low inheritance taxes. Therefore, in terms of reducing tax evasion, it is not recommended to abolish already introduced inheritance taxes, but rather to continue levying a moderate inheritance tax.